On the genus Dicasticus Pascoe, 1886 in archipel of São Tomé and Principe (Curculionidae, Entiminae, Peritelini). - (:unkn) unknown (My University, 2022)
The Afrotropical genus Dicasticus Pascoe, 1886 from São Tomé island is reviewed, redescribed, and four new species from São Tomé are described: D. bonneaui sp. n., D. filippii sp. n., D. nevei sp. n. & D. pearlsteini sp. n. The only already known species from the island, D. verruculatus (Karsch, 1881) is redescribed. All species are illustrated and a key to their identification is provided.
Keywords: African Research